2018
DOI: 10.1016/j.foodchem.2017.11.078
|View full text |Cite
|
Sign up to set email alerts
|

Stability of alternariol and alternariol monomethyl ether during food processing of tomato products

Abstract: The stability of two Alternaria mycotoxins, alternariol (AOH) and alternariol monomethyl ether (AME), has been investigated during the food processing of tomato products simulating commercial processing conditions. The production stages assessed were the storage of raw fruits, fruit washing, and thermal processing. It was observed that time of storage significantly reduced the initial concentration of AOH, but only if tomatoes were stored at 35 °C. For AME, 12 h were sufficient to reduce the initial concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 16 publications
1
17
0
1
Order By: Relevance
“…Similarly, the loss of OTA, ZEA, AFB1, BEA, and ENNs in the products showed that thermal processing effectively decreased the content of these mycotoxins [ 52 , 56 , 57 ]. The 54% AOH reduction was reported for treatment at 110 °C for 20 min, whereas no significant effect was found for AME at the same temperature [ 58 ]. Based on Stadler et al [ 59 ], the parent mycotoxin can be structurally modified during food processing, including isomerization, decarboxylation, rearrangements, and the reaction with other small molecules [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the loss of OTA, ZEA, AFB1, BEA, and ENNs in the products showed that thermal processing effectively decreased the content of these mycotoxins [ 52 , 56 , 57 ]. The 54% AOH reduction was reported for treatment at 110 °C for 20 min, whereas no significant effect was found for AME at the same temperature [ 58 ]. Based on Stadler et al [ 59 ], the parent mycotoxin can be structurally modified during food processing, including isomerization, decarboxylation, rearrangements, and the reaction with other small molecules [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…Catechols formed by hydroxylation of AOH and AME may be further methylated by catechol-O-methyltransferase (Pfeiffer et al 2007;Tiessen et al 2017), while AME was also reported to be demethylated by microsomes of rat, human, and porcine liver (Pfeiffer et al 2007). However, AOH and AME are thermally and chemically rather stable in food matrices and therefore persistent during food processing (Estiarte et al 2018;Siegel et al 2010). Other dibenzopyrones are altenuene (ALT) and its isoform isoaltenuene (isoALT).…”
Section: Introductionmentioning
confidence: 99%
“…For the genotoxic AOH and AME, estimated exposure levels indicated a possible health concern (EFSA, 2011(EFSA, , 2016. These toxins were also shown to be chemically relatively stable during food processing (Estiarte et al, 2018;Siegel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%